An Artificial Intelligence Tutor: A Supplementary Tool for Teaching and Practicing Braille. (September 2016) - McCarthy, Tessa; Rosenblum, L. Penny; Johnson, Benny G.; Dittel, Jeffrey; Kearns, Devin M.
Introduction: This study evaluated the usability and effectiveness of an artificial intelligence Braille Tutor designed to supplement the instruction of students with visual impairments as they learned to write braille contractions. Methods: A mixed-methods design was used, which incorporated a single-subject, adapted alternating treatments design as well as qualitative teacher interviews and surveys. Results: Students seemed to reach 100% accuracy faster when using Braille Tutor (average = 7.0 sessions; range 1.0 to 12.0 sessions) than when they did not (average 9.6 sessions with a teacher of students with visual impairments; range 3.0 to 16.0 sessions). Also, students who used Braille Tutor more often tended to learn more contractions overall during the study (average = 21.25; range 13.0 to 30.0) than students who used it less (average 9.0; range 9.0 to 9.0). Discussion: The first trend noted was that students in the teacher of students with visual impairments plus Braille Tutor phase (hereafter, TVI+Tutor) tended to learn contractions more quickly. A second trend surfaced: The students in the TVI+Tutor phase tended to get more frequent reinforcement as opposed to students in the TVI Only phase. A third trend was noted: Students in the TVI+Tutor phase saw a quicker initial jump and tended to be more consistent in that initial jump. Although the prototype version of Braille Tutor in this study needs further development to broaden its capabilities, some students found its use highly motivating. Implications for practitioners: Although there is strong evidence that advanced technologies are not suitable replacements for braille literacy instruction, technology can be used along with quality instruction by a teacher of visually impaired students to enhance proficiency in braille literacy.